2010
DOI: 10.2478/v10042-009-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ghrelin, GHS-R, GH, and neurohormones in human fetal pituitary glands and central nervous system: an immunohistochemical study.

Abstract: Abstract:The aim of this work was evaluation of expression of ghrelin and GHS-R1a receptor in somatotrops and in neuronal cells of brain tissue in the process of human fetal ontogenesis. Relations were also looked for between GHRH and SS in the pituitary and in the CNS neurones of the studied fetuses. The study was based on 8 pituitaries and 8 brains from fetuses in different periods of intrauterine life. The immunocytochemical technique was used. The presence of ghrelin, GHS-R was shown in the glandular part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our previous research on human foetuses demonstrated that stimulation of GH1 secretion by ghrelin is independent of the feedback control and these two hormones act as a metabolic balance signal [3,23]. In adults, the hypothalamic pituitary axis regulates pulse secretion of GH1 from the pituitary gland, but in foetuses is not functionally mature before the third trimester of pregnancy, independent of earlier anatomical differentiation [3].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research on human foetuses demonstrated that stimulation of GH1 secretion by ghrelin is independent of the feedback control and these two hormones act as a metabolic balance signal [3,23]. In adults, the hypothalamic pituitary axis regulates pulse secretion of GH1 from the pituitary gland, but in foetuses is not functionally mature before the third trimester of pregnancy, independent of earlier anatomical differentiation [3].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Growth processes are relatively well recognised in the postnatal phase, where the key endocrine factor controlling growth is the growth hormone 1/insulinlike growth factor 1 (GH1/IGF-1) axis [1]. Considerably less is known about the mechanisms controlling growth in foetal life in which IGF-1 does not work in conjunction with GH1 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…51,52 It is clear that the primary source of circulating ghrelin is the gastrointestinal tract; however, ghrelin is also produced within the pituitary 6,53-56 and in neurons within the hypothalamus. 6,[55][56][57] In fact, fasting enhances pituitary expression of ghrelin, as well as increasing hypothalamic and pituitary expression of GHS-R. 6,56 Therefore, it is possible that local changes in ghrelin synthesis and sensitivity may play a significant role in promoting GH release in response to fasting. In addition, the hypothalamus and pituitary express GOAT, and transcript levels in both tissues are increased in the fasted mouse, 56 favoring the possibility that local conversion of desacyl to acyl ghrelin could take place to promote GH secretion.…”
Section: Figure 1 the Impact Of Metabolic Extremes On Gh-axis Functimentioning
confidence: 99%
“…It is clear that the primary source of circulating ghrelin is the gastrointestinal tract; however, ghrelin is also produced within the pituitary 6,53–56 and in neurons within the hypothalamus 6,55–57 . In fact, fasting enhances pituitary expression of ghrelin, as well as increasing hypothalamic and pituitary expression of GHS‐R 6,56 .…”
mentioning
confidence: 99%
“…Alternatively, GH-regulating peptides are given continuously, despite the fact that physiological patterns of GHRH and SST release into hypothalamo-pituitary portal blood are significantly pulsatile in the rat, pig, monkey, and sheep (13). Whether hypothalamic and/or intrapituitary ghrelin release is pulsatile is not known (17), but continuous ghrelin/GHRP infusion sustains pulsatile GH secretion in older men and women for 1-3 mo (4). This background raises the question how pulsatile GHRH and SST signals interact with nearly continuous GHRP stimulation.…”
mentioning
confidence: 99%